Refractive outcomes of intraoperative wavefront aberrometry versus optical biometry alone for intraocular lens power calculation - Zina Zhang; Logan William Thomas; Szu-Yen Leu; Steven Carter; Sumit Garg (Indian Journal of Ophthalmology, 2017)
Purpose: To compare the outcomes of intraoperative wavefront aberrometry versus optical biometry alone for intraocular lens (IOL) power calculation in eyes undergoing cataract surgery with monofocal IOL implantation. Methods: Preoperative data were obtained with the IOLMaster. Intraoperative aphakic measurements and IOL power calculations were obtained in some patients with the optiwave refractive analysis (ORA) system. Analysis was performed to determine the accuracy of monofocal IOL power prediction and postoperative manifest refraction at 1 month of the ORA versus IOLMaster. Results: Two hundred and ninety-five eyes reviewed, 61 had only preoperative IOLMaster measurements and 234 had both IOLMaster and ORA measurements. Of these 234 eyes, 6 were excluded, 107 had the same recommended IOL power by ORA and IOLMaster. Sixty-four percent of these eyes were within ±0.5D. 95 eyes had IOL power implantation based on ORA instead of IOLMaster. Seventy percent of these eyes were within ±0.5D of target refraction. 26 eyes had IOL power chosen based on IOLMaster predictions instead of ORA. Sixty-five percent were within ±0.5D. In the group with IOLMaster without ORA measurements, 80% of eyes were within ±0.5D of target refraction. The absolute error was statistically smaller in those eyes where the ORA and IOLMaster recommended the same IOL power based on preoperative target refraction compared to instances in which IOL selection was based on ORA or IOLMaster alone. Neither prediction errors were statistically different between the ORA and IOLMaster alone. Conclusion: Intraoperative wavefront aberrometry with the ORA system provides postoperative refractive results comparable to conventional biometry with the IOLMaster for monofocal IOL selection.